Colonization, whenua and capitalism: experiences from Aotearoa New Zealand - Moewaka Barnes, Helen; Eich, E.; Yessilth, S. (Continuum, 2018)
The English Laws Act, passed in 1858, declared the Laws of England applicable in New Zealand and cemented the hitherto alien ideology of land as property. Part of this ideology was the separation of tangata from whenua along with the separation of ownership of land from ownership of water. Māori, as tangata whenua – people of the land, made no such distinctions. Ownership affects how people ‘manage’ whenua (land), make decisions and account to the legal system. Under English law, financial considerations are at the forefront. In contrast, Māori kaitiakitanga values are concerned with the interests of land, understanding that the best interests of people will follow. Despite stark contrasts between the ideology of land as property and the ethics of kaitiakitanga – obligation, sustainability and nurture – Māori engage with mainstream agencies and lead by example in efforts to promote the wellbeing of people and environments in a unified approach. This paper outlines competing paradigms, changing relationships and challenges faced by communities who seek to nurture and respect whenua in the face of colonization. Interview data from Māori involved in community land-based initiatives illustrates past and present struggles and what some possibilities might be for the future.
Keywords: capitalism; colonisation; crown law; kaitiakitanga; whenua

The face behind the law: The United Nations and the rights of indigenous peoples - Jackson, Moana (Yearbook of New Zealand jurisprudence, 2005)
In recent years Maori people have adopted many strategies to protect and advance the well being and visions implicit in the exercise of tino rangatiratanga. Much of that work has been done at home, but an increasing number of Iwi and other Maori organisations are now participating in international affairs that are seen to have some relevance to our lives. They are joining a worldwide movement by Indigenous Peoples to reassert their rights and reclaim their rightful place.
Keywords: UNDRIP; civil Rights; colonisation; crown law; imperialism; international law; international organization; racism; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Maori rights: legal or political? - Charters, Claire (Public law review (North Ryde, N.S.W.), 2015)
Willingness of New Zealand courts to enforce legal rights where a political mechanism to address Maori rights exists - land rights - human rights - political rights - principles of the Treaty of Waitangi - takanga.
Keywords: crown law; human rights; land rights

A Self-Determination Approach to Justifying Indigenous Peoples' Participation in International Law and Policy Making - Charters, Claire (International journal on minority and group rights, 2010)
This paper defends the legitimacy-positive impact of a "contextual-participation approach" to indigenous peoples' participation in international law-making. It argues that indigenous peoples' participation should be substantial where the issue being negotiated at the international level is of considerable interest to indigenous peoples and indigenous peoples have not consented to state representation. The "contextual-participation approach" to indigenous peoples' participation realises the justice in indigenous peoples' claims to remedial efforts to recognise their, mostly lost and historical, sovereignty, and to contemporary and evolving legal, and largely democratic, understandings of self-determination, as expressed, for example, in the UN Declaration on the Rights of Indigenous Peoples. At the same time, it balances indigenous peoples' self-determination entitlements to full participation in international law making, as unjustifiably excluded sovereigns, with contemporary political realities.
Keywords: autonomy; crown law; human rights; indigenous rights; international law; international relations; justice; law; not sure if maori; participation; policy making; political activity; political participation; representation; right wing politics; rights; self-determination; sovereignty; united nations

Report from the inside: the CERD Committee's review of the Foreshore and Seabed Act 2004 - Charters, Claire; Erueti, Andrew (Law review (Wellington), 2005)
Describes, from the perspective of the advocates for Maori claimants, the substance of submissions to and process followed by the United Nations committee on the Elimination of Racial Discrimination (CERD) in determining that the Foreshore and Seabed Act 2004 discriminates against Maori. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: civil Rights; crown law; foreshore and seabed act 2004; human rights; international law; international organization; land rights; land tenure; racism

Rights, interests and expectations: Indigenous perspectives on unrestricted access to genomic data - Hudson, Maui; Garrison, Nanibaa’ A.; Sterling, Rogena; Caron, Nadine R.; Fox, Keolu; Yracheta, Joseph; Anderson, Jane; Wilcox, Phil; Arbour, Laura; Brown, Alex; Taualii, Maile; Kukutai, Tahu; et al. (Nature Reviews Genetics, 2020)
Addressing Indigenous rights and interests in genetic resources has become increasingly challenging in an open science environment that promotes unrestricted access to genomic data. Although Indigenous experiences with genetic research have been shaped by a series of negative interactions, there is increasing recognition that equitable benefits can only be realized through greater participation of Indigenous communities. Issues of trust, accountability and equity underpin Indigenous critiques of genetic research and the sharing of genomic data. This Perspectives article highlights identified issues for Indigenous communities around the sharing of genomic data and suggests principles and actions that genomic researchers can adopt to recognize community rights and interests in data.
Keywords: crown law; data sovereignty; ethics; genes; genetic databases; genomic sequencing; population genetics